Development of a Home-based Learning Set for Promoting the Development of Fine Motor and Intelligence, and Concentration in Early Childhood - Wannachot, Jariyaphon; Boonchuaylua, Pattama; Khammarit, Supa (Journal of Phrapokklao Nursing College, Chanthaburi, 2022)
This research and development aimed to develop and study the effectiveness of a home-based learning set for promoting the development of fine motor and intelligence, and concentration in early childhood. There were five phases of research including: 1) exploring problems and needs of parents; 2) developing a home-based learning set for promoting the development of fine motor and intelligence, and concentration in early childhood; 3) trying out a home-based learning set with 10 couples of parents and children; 4) improving a home-based learning set; and 5) evaluating a home-based learning set with 30 couples of parents and children of Child Development Center, Phrapokklao Nursing College, Chanthaburi. The research instruments consisted of a semi-structured interview form, a home-based learning set for promoting the development of fine motor and intelligence, and concentration in early childhood, a demographic record form, a development of fine motor and intelligence assessment form with reliability of .88, and a concentration assessment form with reliability of .74. The implementation and data collection were conducted from September, 2021 to January, 2022. Data were analyzed using frequency, percentage, mean, standard deviation, and paired t-test. The research results revealed that 1) a home-based learning set for promoting the development of fine motor and intelligence, and concentration in early childhood consisted of five sets: (1) animal photo jigsaw, (2) string of numbers, (3) molding plasticine by numbers, (4) hand writing exercises, and (5) math exercises; 2) after implementing each home-based learning set, children had statistically significantly higher mean score of development of fine motor and intelligence than that of before implementing each home-based learning set (p < .001); and 3) after implementing home-based learning set, children had statistically significantly more concentration in each item than that of before implementing home-based learning set (p < .001). This research suggests that early childhood teachers should apply this home-based learning set to promote the development of fine motor and intelligence, and concentration in early childhood of other child development centers.